Isolated, displaced, talar body fracture: a case report and literature review - Mosca, Angelo; Pessina, Fabio; Ragni, Paolo; Cazzaniga, Carlo; Cardile, Carlo (Acta Biomedica Atenei Parmensis, 2023)
Talar body fractures are uncommon fractures of the foot and its management results to be very hard due to retrograde vascularization and wide articular cartilage coverage of talar surface, which could easily lead to poor functional outcomes, avascular osteonecrosis and early post traumatic arthritis. We describe a case of displaced, vertical, talar body fracture in a 41-year-old patient treated with reduction and fixation by talar anteromedial approach coupled to medial malleolar osteotomy to better expose the fracture. Our literature review has found few studies, in addition with a low level of statistical evidence. We advocate for more studies with a bigger sample and with a design of randomized control trials